Volume 4A: Combustion, Fuels and Emissions 2017
DOI: 10.1115/gt2017-63131
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fuel Composition and Altitude Impact on Gaseous and Particle Emissions From a Turbojet Engine

Abstract: The effects of altitude and fuel composition on gaseous and particle emissions from a turbojet engine were investigated as part of the National Jet Fuels Combustion Program (NJFCP) effort. Two conventional petroleum based jet fuels (a “nominal” and a “worst-case” jet fuel) and two test fuels with unique characteristics were selected for this study. The “worst-case” conventional jet fuel with high flash point and viscosity resulted in reduced combustion efficiency supported by the reduced CO2 emissions and corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A decrease in aromatic content typically causes the hydrogen content to increase which would also affect the nonvolatile particle number emissions . In a lab experiment, Chan et al found that the fuel hydrogen content provided the best correlation with black carbon emission indices . Although both hydrogen and aromatic content affect particle number emissions, they are interdependent (decreasing aromatic content tends to increase the hydrogen/carbon ratio) and therefore it is difficult to credit either one as the main reason for the reduction in particles with the ATJ-SPK blend …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in aromatic content typically causes the hydrogen content to increase which would also affect the nonvolatile particle number emissions . In a lab experiment, Chan et al found that the fuel hydrogen content provided the best correlation with black carbon emission indices . Although both hydrogen and aromatic content affect particle number emissions, they are interdependent (decreasing aromatic content tends to increase the hydrogen/carbon ratio) and therefore it is difficult to credit either one as the main reason for the reduction in particles with the ATJ-SPK blend …”
Section: Resultsmentioning
confidence: 99%
“…14 In a lab experiment, Chan et al found that the fuel hydrogen content provided the best correlation with black carbon emission indices. 32 Although both hydrogen and aromatic content affect particle number emissions, they are interdependent (decreasing aromatic content tends to increase the hydrogen/carbon ratio) 14 and therefore it is difficult to credit either one as the main reason for the reduction in particles with the ATJ-SPK blend. 12 Also shown in Figure 2, it can be seen that the JP-5 fuel emissions are comparable to Jet A1 fuel.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it should be considered that increasing the proportion of hydrogen in the fuel also reduces the formation of particulate matter in the soot mode. Reducing the share of aromatics results in an increase in the H/C ratio, therefore it is difficult to say what influences the PM emission to a greater extent [30,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…For this study, three different liquid aviation fuels were used: Jet A1 (POSF10325), Gevo ATJ (POSF11498), and a custom fuel that will be referred to as "C10" (POSF12345) due to its 74% composition of C10 iso-paraffins. As of 2021, Jet A1 is the only fuel cleared to be used in commercial aircraft [10], but the ATJ and C10 fuels are currently being used by the National Jet Fuels Combustion Program (NJFCP) as potential SAFs for future commercial use [54]. For this study, Jet A1 was chosen as a benchmark fuel, the ATJ was chosen as it is an approved biojet fuel for mixture with Jet A1 and operated on noncommercial flights, and the C10 was chosen because of its high aromatic content.…”
Section: Fuels and Flame Conditionsmentioning
confidence: 99%
“…Mixing between the two flows takes place and the collected sample is diluted. .... 25 Figure 2.5: Alkane and aromatic mass percent composition of the three test fuels [54]. .…”
mentioning
confidence: 99%